New perspectives on late antiquity in the Eastern Roman Empire - Francisco Heredero, Ana de.; Hernández de la Fuente, David A.; Torres Prieto, Susana. (Cambridge Scholar Publishing, 2014)
The present volume presents some of the latest research trends in the study of Late Antiquity in the Eastern Roman Empire from a multi-disciplinary perspective, encompassing not only social, economic and political history, but also philology, philosophy and legal history. The volume focuses on the interaction between the periphery and the core of the Eastern Empire, and the relations between Eastern Romans and Barbarians in various geographic areas, during the approximate millennium that elap ...